ANALISIS PENGARUH PRICE TO BOOK VALUE PADA PT SURYA CITRA MEDIA DITINJAU BERDASARKAN FAKTOR RETURN ON EQUITY, NET PROFIT MARGIN DAN DEBT TO EQUITY RATIO - Fakung Rahman; Agus Supriatna; Tiffani Novia Rachmi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study aims to determine the effect of Return On Equity (ROE), Net Profit Margin (CR), and Debt to Equity Ratio (DER) on Price to Book Value (PBV) at PT Surya Citra Media Tbk for period of 2011-2020. The data used is sourced from the financial statements of the company. In this study the authors used quantitative research. The data analysis technique used in this study is multiple linear regression with the help of computer software, namely Statistical Product and Service Solutions (SPSS) Version 23. The sampling technique used was purposive sampling method with certain criteria and obtained a sample of 10 financial statements of PT Surya Citra Media Tbk year 2011-2020. The results of multiple linear regression analysis shows that Return On Equity (ROE) has no effect on Price to Book Value (PBV), Net Profit Margin (NPM) has no effect on Price to Book Value (PBV), while Debt to Equity Ratio (DER) positive effect on Price to Book Value (PBV). And together ROE, NPM and DER have no effect on PBV. The conclusion of this study is that the ROE, NPM and DER variables affect PBV only by 30.89% while 69.11% is determined by other factors from outside the company.